2000
DOI: 10.3109/15419060009040302
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of αvβT3, αvβTB5 Integrins and the Integrin Associated Protein — IAP (CD47) in Human Glomerular Diseases

Abstract: The a v integrins present on the membrane of numerous cells, mediate attachment to matrix proteins, cell proliferation, migration and survival. We studied the expression of a v integrins and CD47 (a 0 3 chain integrin associated protein) in various forms of glomerulonephritis (GN) characterized by mesangial proliferation and/or increased mesangial matrix. In normal glomeruli, epithelial cells expressed avp3, avP5 and CD47; endothelial cells expressed asp1 and C D 4 7 ; mesangial cells expressed avp5, CD47, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Secreted CCN1, which may be quantified by CCN1 staining at the cytoplasm, can act on glomerular cells in a GBM-bound form, since CCN1 has a high affinity for heparan sulfate proteoglycans (37), a major component of the GBM (8). Furthermore, CCN1 interacts with a variety of integrins (3,9,14,19,28), e.g., acting through integrin ␣ v ␤ 3 on endothelial cells and through ␣ v ␤ 5 on fibroblasts (9,14), both of which are expressed in mesangial cells and podocytes (10). It was recently reported that production of vascular endothelial growth factor A, a homodimeric glycoprotein of 48 kDa, from podocytes is required for mesangial cell survival in vivo (6), suggesting that secreted factors from podocytes can act on glomerular cells, counteracting against the flow from the capillary lumen to the urinary space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secreted CCN1, which may be quantified by CCN1 staining at the cytoplasm, can act on glomerular cells in a GBM-bound form, since CCN1 has a high affinity for heparan sulfate proteoglycans (37), a major component of the GBM (8). Furthermore, CCN1 interacts with a variety of integrins (3,9,14,19,28), e.g., acting through integrin ␣ v ␤ 3 on endothelial cells and through ␣ v ␤ 5 on fibroblasts (9,14), both of which are expressed in mesangial cells and podocytes (10). It was recently reported that production of vascular endothelial growth factor A, a homodimeric glycoprotein of 48 kDa, from podocytes is required for mesangial cell survival in vivo (6), suggesting that secreted factors from podocytes can act on glomerular cells, counteracting against the flow from the capillary lumen to the urinary space.…”
Section: Discussionmentioning
confidence: 99%
“…The transfer vector along with BacPAK6 viral DNA (Clontech) was delivered into cells by liposome-mediated transfection to obtain a recombinant virus. Sf9 cells grown to 10 6 cells/ml in SFM-II medium were infected with the recombinant virus and incubated for 48 h at 28°C. The conditioned media centrifuged at 5,000 g for 5 min at 4°C were adjusted to 50 mM sodium phosphate buffer (pH 6.0) containing 2 mM EDTA and 1 mM PMSF and applied to a Hitrap SP column (Amersham, Piscataway, NJ) at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…In renal diseases including acute postinfectious glomerulonephritis (GN), membranoproliferative GN, and diabetic nephropathy, CD47 expression decreased in mesangial cells (31). CD47 is also markedly decreased during mesangiolysis, but increased in mesangial cells in the restoration stage (60).…”
Section: Tsp1 and Cd47 In Renal Diseasementioning
confidence: 99%
“…In cell culture or with injury, TSP1 is secreted by kidney mesangial cells, a process that can be suppressed by nitric oxide (NO) pro-drugs (96). CD47 is expressed in several renal cell types including epithelial, endothelial, and mesangial cells (31) but not in podocytes (60). It is also expressed in proximal tubular HK-2 cells (7).…”
Section: Distribution Of Tsp1 and Cd47 In The Kidneymentioning
confidence: 99%
“…[25][26][27] In ischemic rat kidneys ␤ 1 and ␣ v ␤ 3 were found to be localized in proximal and distal tubules and endothelium. 27 Also different forms of glomerulonephritis were found to be associated with modifications in their ␣ v integrin expression: the distal tubular expression of ␤ 3 was increased, and a de novo appearance of ␣ v ␤ 3 and ␣ v ␤ 5 on proximal tubular cells in comparison to normal kidneys was noticed 24,43 ; ␣ v ␤ 6 , which is exclusively expressed by epithelial cells, was elevated in the kidney epithelium of patients with membranous glomerulonephritis, IgA nephropathy, and in acute and chronic rejection of human kidney allografts. 44, 45 By immunostaining we could show the increased expression of ␣ v ␤ 3 in rejecting rat kidney allografts, in peritubular capillaries, on the endothelial surface of preglomerular arteries and in tubular epithelial cells in comparison to normal F344 kidneys as well as its presence in the intragraft perivascular cellular infiltrate.…”
Section: Discussionmentioning
confidence: 99%